Human DNA sequence homologous to the transforming gene (mos) of Moloney murine sarcoma virus. - Watson, R (1982)
We describe the molecular cloning of a 9-kilo-base-pair BamHI fragment from human placental DNA containing a sequence homologous to the transforming gene (v-mos) of Moloney murine sarcoma virus. The DNA sequence of the homologous region of human DNA (termed humos) was resolved and compared to that of the mouse cellular homolog of v-mos (termed mumos) [Van Beveren, C., van Straaten, F., Galleshaw, J.A. & Verma, I.M. (1981) Cell 27, 97-108]. The humos gene contained an open reading frame of 346 codons that was aligned with the equivalent mumos DNA sequence by the introduction of two gaps of 15 and 3 bases into the mumos DNA and a single gap of 9 bases into the humos DNA. The aligned coding sequences were 77% homologous and terminated at equivalent opal codons. The humos open reading frame initiated at an ATG found internally in the mumos coding sequence. The polypeptides predicted from the DNA sequence to be encoded by humos and mumos also were found to be extensively homologous, and 253 of 337 amino acids were shared between the two polypeptides. The first five NH2-terminal and last two COOH-terminal amino acids of the humos gene product were in common with those of mumos. In addition, near the middle of the polypeptide chains, four regions ranging from 19 to 26 consecutive amino acids were conserved. However, we have not been able to transform mouse cells with transfected humos DNA fragments or with hybrid DNA recombinants containing humos and retroviral long terminal repeat (LTR) sequences.